KAJIAN BIAYA OPERASIONAL KENDARAAN ANGKUTAN PENUMPANG UMUM KOTA MALANG - Khoirul Abadi (Media Teknik Sipil, 2012)
Almost of Malang public passenger transport vehicles (APU) that operates has reached 17years or more. APU renewal vehicles opinion offered by the Government has always rejected by theoperator. Though Performance of a city depends on the quality of transportation system performance,including the performance of public passengers transportation. This study aimed to produce aconstructive information to support the APU vehicles renewal in public passenger transport operationMalang better. This study has an empirical method, refers to the decision of Director General ofLand Transportation No.687/AJ.206/DRJD/2002 and the Minister of Transportation Decree No.89/2002. The results of the study showed that the average of the vehicle operating costs (renewalvehicles) is Rp. 121,906,736, -/year or Rp. 1.671, -/km. Based on the average of the number ofpassengers (actual), it is shown that the difference of the average between acceptance of the tariffand the vehicle operating cost is Rp. 143,121.79 per-vehicle per-day.Keyword: public passenger transport, vehicle operating cost